Tin oxide for optoelectronic, photovoltaic and energy storage devices: a review. Issue 31 (2nd August 2021) - Dalapati, Goutam Kumar; Sharma, Himani; Guchhait, Asim; Chakrabarty, Nilanjan; Bamola, Priyanka; Liu, Qian; Saianand, Gopalan; Sai Krishna, Ambati Mounika; Mukhopadhyay, Sabyasachi; Dey, Avishek; Wong, Terence Kin Shun; Zhuk, Siarhei; et al.
Abstract : Tin dioxide (SnO2 ) used in various applications due to suitable band gap and tunable conductivity. It has excellent thermal, mechanical and chemical stability. Abstract : Tin dioxide (SnO2 ), the most stable oxide of tin, is a metal oxide semiconductor that finds its use in a number of applications due to its interesting energy band gap that is easily tunable by doping with foreign elements or by nanostructured design such as thin film, nanowire or nanoparticle formation, etc., and its excellent thermal, mechanical and chemical stability. In particular, its earth abundance and non-toxicity make it very attractive for use in a number of technologies for sustainable development such as energy harvesting and storage. This article attempts to review the state of the art of synthesis and properties of SnO2, focusing primarily on its application as a transparent conductive oxide (TCO) in various optoelectronic devices and second in energy harvesting and energy storage devices where it finds its use as an electron transport layer (ETL) and an electrode material, respectively. In doing so, we discuss how tin oxide meets the requirements for the above applications, the challenges associated with these applications, and how its performance can be further improved by adopting various strategies such as doping with foreign metals, functionalization with plasma, etc. The article begins with a review on the various experimental approaches to doping of SnO2 with foreign elements for its enhanced performance as a TCO as well as related computational studies. Herein, we also compare the TCO performance of doped tin oxide as a function of dopants such as fluorine (F), antimony (Sb), tantalum (Ta), tungsten (W), molybdenum (Mo), phosphorus (P), and gallium (Ga). We also discuss the properties of multilayer SnO2 /metal/SnO2 structures with respect to TCO performance. Next, we review the status of tin oxide as a TCO and an ETL in devices such as organic light emitting diodes (OLEDs), organic photovoltaics (OPV), and perovskite solar cells (including plasma treatment approaches) followed by its use in building integrated photovoltaic (BIPV) applications. Next, we review the impact of SnO2, mainly as an electrode material on energy storage devices starting from the most popular lithium (Li)-ion batteries to Li–sulfur batteries and finally to the rapidly emerging technology of supercapacitors. Finally, we also compare the performance of doped SnO2 with gallium (Ga) doped zinc oxide (ZnO), the main sustainable alternative to SnO2 as a TCO and summarize the impact of SnO2 on circular economies and discuss the main conclusions and future perspectives. It is expected that the review will serve as an authoritative reference for researchers and policy makers interested in finding out how SnO2 can contribute to the circular economy of some of the most desired sustainable and clean energy technologies including the detailed experimental methods of synthesis and strategies for performance enhancement.